Emergence of Supranational Powers Melts the Political Regime of Freedoms: Media Views Regarding the Shake-up of Democracy (London Journal of Research In Humanities and Social Sciences, 2024)
The perception of journalistic media regarding government measures has the potential to shape the culture of a society and determine actions favorable or against democracy. The way in which narratives are constructed, whether with attributes of positive or negative polarity, serves as a thermometer in relation to the direction of decisions and their political and socioeconomic consequences. From the middle of the last decade, the emphasis on the demands of journalistic making, including discourses and debates on social networks, began to privilege the need to protect thesignifier of democracy, reaching the point of eroding its meaning, opening up space for contrary powers to collective and, particularly, individual freedoms. In view of this, new concepts emerge and shake the supporting tripod of democracy, providing opportunities for the advance of the tentacles of supranational powers. When check thewatchwords built by the media enunciators on digital platforms since 2020, one can understand the scenario created with a view to breaking with the democratic regime, tracing a boundary line between before and after, between democracy and authoritarianism.
Keywords: Higher education; innovations in education; Russian educational policy; Russian-centric model of education.; Democracy; support tripod; press; supranational power; discourse engineering